Answer:

Step-by-step explanation:
I assume that you need simplification of the given expression.
The given expression is:

Using distributive property and multiplying 2 inside the parenthesis and 1 inside the other parenthesis. This gives,

Therefore,
is equal to:

Now, combining like terms using the commutative property of addition, we get:

Therefore, the simplified form is 
For the fulcrum to balance, the product of weight and distance on both sides of the fulcrum must be the same.
Let d1= x. since total distance is 12, we can write d2 = 12 - x
for the fulcrum to balance:
60x = 50(12 - x)
60x = 600 - 50x
110x = 600
x = 5.45
Thus, d1= 5.45
and
d2= 12 - d1 = 12 - 5.45 = 6.55
d1 = 5.45
d2 = 6.55